2020
DOI: 10.1111/add.15233
|View full text |Cite
|
Sign up to set email alerts
|

African Americans now outpace whites in opioid‐involved overdose deaths: a comparison of temporal trends from 1999 to 2018

Abstract: Aims To estimate racial differences in rates of opioid‐involved overdose deaths (OOD) between whites and African Americans in the United States from 1999 to 2018 to (1) identify racial variation in the temporal trends of OOD during the 20‐year period and (2) compare trends in OOD rates between whites and African Americans using the Centers for Disease Control and Prevention's (CDC) three defined OOD epidemic periods. Methods Data were obtained from the CDC wide‐ranging on‐line data for epidemiological research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
71
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(80 citation statements)
references
References 12 publications
9
71
0
Order By: Relevance
“…However, recent findings have indicated that Black communities are being strongly impacted. This research has indicated that opioid overdoses among Black persons are now outpacing White persons (Furr-Holden et al, 2021;Milam et al, 2021), indicating that a major brunt of the issue may be impacting Black communities. These findings add to this literature and indicate the continued need to understand not only risk for use, but also understand how risk for use may not tell the full story.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent findings have indicated that Black communities are being strongly impacted. This research has indicated that opioid overdoses among Black persons are now outpacing White persons (Furr-Holden et al, 2021;Milam et al, 2021), indicating that a major brunt of the issue may be impacting Black communities. These findings add to this literature and indicate the continued need to understand not only risk for use, but also understand how risk for use may not tell the full story.…”
Section: Discussionmentioning
confidence: 99%
“…Opioid use, including both illicit opioid use and prescription opioid misuse, and overdose deaths among Black individuals are continuing to increase at alarmingly high rates and differentially by gender [15][16][17][18]. Between 2010 and 2017, Black individuals experienced the largest increase in drugrelated overdose deaths [19].…”
Section: Introductionmentioning
confidence: 99%
“…These deaths are probably related to the fact that fentanyl and fentanyl analogs have very high affinity for μ-opioid receptors and are therefore extremely toxic when consumed in large quantities because of their interactions with receptors located in brain regions that control respiration. It is important to point out that during the time of increased fentanyl abuse and drug-induced fatal overdoses, there were African American subgroups that have been reported to surpass other ethnic groups in terms of fentanyl-associated overdose deaths (Carlesso and Kara, 2019 ; Lippold et al, 2019 ; Chau, 2020 ; DeLaquil, 2020 ; Furr-Holden et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%